Substantive Due Process Protection at the Outer Margins of Municipal Behavior - Brian W. Blaesser (Washington University Journal of Law & Policy, 2000)
Realistically, the landowner and developer know that the review of a development project in light of today’s more complex land use, growth, and environmental considerations requires in many cases the ingredient of human judgment in order to provide pragmatic resolution of these issues. There is always a tension between landowners’ and developers’ preferences for certainty on the one hand and on the other hand their need for pragmatic solutions that only the exercise of judgment can provide.
Keywords: Due process of law; Land use; Zoning law